2017
DOI: 10.1002/slct.201601538
|View full text |Cite
|
Sign up to set email alerts
|

Platinum functionalized Chiral Polyamides: Efficient Heterogeneous Catalyst for Solvent Free Asymmetric Hydrogenation of Ethyl 2‐oxo‐4‐phenylbutanoate

Abstract: The present study highlights platinum nanoparticles incorporated chiral polyamide for asymmetric hydrogenation of carbonyl group. Chiral polyamides are synthesized from chiral monomers, camphoric dichloride and achiral diamine monomers by interfacial condensation reaction. This chiral polyamide supports have helical structure with molecular chirality. The polyamide helices provide chiral environment to platinum nanoparticles that transfer to substrate during catalytic hydrogenation. The chemical and optical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Sharma et al described the preparation of chiral polyamides by interfacial polycondensation reaction of chiral camphoric dichloride and various diamines. [52] Platinum (Pt) nanoparticles (NPs) were subsequently incorporated into the chiral polyamide for asymmetric hydrogenation of ethyl 2-hydroxy-4phenylbutanoate. In this work, chiral camphoric dichloride was prepared from camphoric acid and thionyl chloride because the dichloride was more suitable for the reaction with diamines under ambient conditions.…”
Section: Interfacial Polycondensationmentioning
confidence: 99%
See 3 more Smart Citations
“…Sharma et al described the preparation of chiral polyamides by interfacial polycondensation reaction of chiral camphoric dichloride and various diamines. [52] Platinum (Pt) nanoparticles (NPs) were subsequently incorporated into the chiral polyamide for asymmetric hydrogenation of ethyl 2-hydroxy-4phenylbutanoate. In this work, chiral camphoric dichloride was prepared from camphoric acid and thionyl chloride because the dichloride was more suitable for the reaction with diamines under ambient conditions.…”
Section: Interfacial Polycondensationmentioning
confidence: 99%
“…[84] As discussed in Section 2, some chiral polyamides can adopt a helical conformation. [22,51,52,54,55] For example, Park et al reported an interesting strategy for the synthesis of helical nylons and polyphthalamides with one-handed spiral morphologies. [51] That is, a chiral reaction field based on N*-LC was used for the chiral interfacial polycondensation.…”
Section: Helical Polyamidesmentioning
confidence: 99%
See 2 more Smart Citations
“…The racemic product was obtained in the absence of the chiral inducer (Table 1, entry 2), which indicated the importance of the inducer in the chiralinduction process. The chiral inducer is crucial to provide a chiral atmosphere in asymmetric reduction, 27 resulting in high enantioselectivity with a high asymmetric inducer concentration around the cathode. The ee values obtained from the D-PHE-MWCNTs (Table 1, entries 3−6) were markedly higher than those of p-MWCNTs (Table 1, entry 1), indicating that the functionalized MWCNTs cathodes were more beneficial as heterogeneous materials.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%